A balanced dietary amino acid profile improves amino acid retention in post-larval Senegalese sole (Solea senegalensis) - Aragão, C. (2014)
The rearing of most marine fish larvae still relies on live food. Dietary amino acid (AA) imbalances when using live food in the larval rearing of flatfishes have been suggested. The aim of this study was to test if dietary AA supplementation affects AA metabolism in Senegalese sole (Solea senegalensis) post-larvae. This was done by tube-feeding Artemia-fed sole with a dipeptide solution containing two potential limiting AA (leucine and phenylalanine), in order to supplement the larval gut content and to balance the dietary AA profile.